2019
DOI: 10.1111/tpj.14592
|View full text |Cite
|
Sign up to set email alerts
|

Two ANGUSTIFOLIA genes regulate gametophore and sporophyte development in Physcomitrella patens

Abstract: Summary In Arabidopsis thaliana the ANGUSTIFOLIA (AN) gene regulates the width of leaves by controlling the diffuse growth of leaf cells in the medio‐lateral direction. In the genome of the moss Physcomitrella patens, we found two normal ANs (PpAN1‐1 and 1‐2). Both PpAN1 genes complemented the A. thaliana an‐1 mutant phenotypes. An analysis of spatiotemporal promoter activity of each PpAN1 gene, using transgenic lines that contained each PpAN1‐promoter– uidA (GUS) gene, showed that both promoters are mainly ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Cell Phenotype Are Synergistically Enhanced in an-1 fugu5-1 ANGUSTIFOLIA (AN) is the sole homolog of CtBP/BARS in Arabidopsis. The CtBP/BARS protein family has diverse functions, intercellular localization, and developmental role in a wide range of land plants (Kim et al, 2002;Minamisawa et al, 2011;Furuya et al, 2018;Hashida et al, 2019). AN regulates the width of Arabidopsis leaves by controlling the polar elongation of leaf cells.…”
Section: Cotyledon Development and Pavementmentioning
confidence: 99%
“…Cell Phenotype Are Synergistically Enhanced in an-1 fugu5-1 ANGUSTIFOLIA (AN) is the sole homolog of CtBP/BARS in Arabidopsis. The CtBP/BARS protein family has diverse functions, intercellular localization, and developmental role in a wide range of land plants (Kim et al, 2002;Minamisawa et al, 2011;Furuya et al, 2018;Hashida et al, 2019). AN regulates the width of Arabidopsis leaves by controlling the polar elongation of leaf cells.…”
Section: Cotyledon Development and Pavementmentioning
confidence: 99%
“…In our previous study (Hashida et al, 2020), we found four genes that were homologous to AtAN in the P. patens genome.…”
Section: Introductionmentioning
confidence: 84%
“…These data indicate that neither PpAN2 gene was highly expressed (RPKM > 1500). Because the values of RPKM were approximately 10-20 for the PpAN1 genes (Hashida et al, 2020), expression of the PpAN2 genes was relatively low.…”
Section: Expression Pattern Of Ppan2 Genesmentioning
confidence: 99%
See 2 more Smart Citations